THE IMPACT OF KOREAN CULTURE ON UZBEK PEOPLE - Nag'matullayeva Ra'no; Maftuna Nurova (TADQIQOTLAR, 2025)
Annotation  In  today's  world,  motivating  people  and  laborers  in  their  individual  and  proficient lives is pivotal. This paper investigates how Korean culture, particularly by  means of media, dialect, and way of life impacts, rouses youthful Uzb